THE EFFORT OF IMPROVING JAPANESE LITERATURE ABILITY OF JAPANESE LITERATURE STUDENTS OF FACULTY OF CULTURAL STUDY UB IN REACHING MONBUKAGAKUSHO SCHOLARSHIP - Efrizal Efrizal (Fakultas Bahasa dan Seni Universitas Negeri Padang, 2014)
For Japanese language learners in Indonesia get Monbukagakusho Japanese Studies program is something that is very coveted. Moreover Monbukagakusho Japanese Studies program through G to G that must be faced through a very strict selection. In 2012 Japanese students of Faculty of Cultural Study UB who pass the selection were 7 students, in 2013 were 4 students, and in 2014 were 8 students graduated from 21 students in Indonesia. To reach the achievement, it is necessary efforts to improve Japanese ability especially Kanji (writing) Bunpou (grammar), and Dokkai (reading comprehension). The development of students’ cognitive ability does not walk alone but it required the ability to organize and control its cognitive abilities. The approach used in this study is metacognitive. From the description above, the research problems are formulated as follows: (1) How to increase Japanese students’ ability who participate monbukagakusho selection, (2) What factors which support the learning systems to improve students’ ability to deal with the selection. The method used in this research is descriptive qualitative. This study used a questionnaire with 30 respondents of Japanese literature student of Faculty of Cultural Study UB who have joined benkyoukai monbukagakusho test preparation. The results showed that to increase the students’ Japanese language proficiency, it is required benkyoukai with strict selection. The students who do not achieve a score above 60% with correct answers 3 (three) times in a row will fall The factors that support learning systems are: The role of the study program, student of benkyoukai participants, materials and evaluation, and facilities and infrastructure. Keywords: benkyoukai (study group), monbukagakusho (scholarship of Ministry of Education and Culture Japan)